2022
DOI: 10.1186/s12651-022-00316-5
|View full text |Cite
|
Sign up to set email alerts
|

Germany and the United States in coronavirus distress: internal versus external labour market flexibility

Abstract: Germany and the United States pursued different economic strategies to minimise the impact of the Coronavirus Crisis on the labour market. Germany focused on safeguarding existing jobs through the use of internal flexibility measures, especially short-time work (STW). The United States relied on a mix of external flexibility and income protection. On this basis, we use macroeconomic time series to examine the German strategy of securing employment through internal flexibility by contrasting it with the chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The handling of the financial crisis of 2008/2009 without any major increase in unemployment became a model for the COVID crisis. Even in smaller companies, including in the service sector with less protection against dismissal, redundancies were avoided in the COVID crisis (Herzog-Stein et al, 2022).…”
Section: Promoting Internal Transformationmentioning
confidence: 99%
“…The handling of the financial crisis of 2008/2009 without any major increase in unemployment became a model for the COVID crisis. Even in smaller companies, including in the service sector with less protection against dismissal, redundancies were avoided in the COVID crisis (Herzog-Stein et al, 2022).…”
Section: Promoting Internal Transformationmentioning
confidence: 99%
“…According to the study findings, Germany firmly emphasized the use of internal flexibility measures, especially short-time work (STW) to safeguarding employment. Moreover, the authors argue that, unlike in the U.S., discretionary changes to unemployment benefits (Social Security Package) have had only a minor impact in securing the income of the unemployed in Germany (Herzog-Stein et al, 2022).…”
Section: The Background -Coronavirus Outbreak and Labor Market Crisismentioning
confidence: 99%
“…Previous research has shown that STW was largely effective in protecting jobs during the previous financial crisis in 2007/2008 (Kopp & Siegenthaler, 2021). The same positive effects seem to have emerged during the COVID-19 pandemic (Herzog-Stein et al, 2022). However, during the times when STW has been used most extensively, media reports have claimed that STW is exploited by employers.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to previous crises, this massive job loss was accompanied by a decline in job search by the unemployed (Forsythe et al, 2020b). Although the German economy was hit very similarly, as its GDP dropped by 9.9% (as compared to 8.9% in the United States) in the second quarter of 2020, its labor market's reaction was relatively modest (Herzog‐Stein et al, 2022). A major difference between the U.S. and the German labor market is often ascribed to the latter's generous use of short‐time work (STW), which allows employers to put workers on hold instead of engaging in massive job terminations.…”
Section: Introductionmentioning
confidence: 99%